Temporal dynamics influenced by global change: bee community phenology in urban, agricultural, and natural landscapes. (14th December 2015) - Leong, Misha; Ponisio, Lauren C.; Kremen, Claire; Thorp, Robbin W.; Roderick, George K.
Abstract: Urbanization and agricultural intensification of landscapes are important drivers of global change, which in turn have direct impacts on local ecological communities leading to shifts in species distributions and interactions. Here, we illustrate how human‐altered landscapes, with novel ornamental and crop plant communities, result not only in changes to local community diversity of floral‐dependent species, but also in shifts in seasonal abundance of bee pollinators. Three years of data on the spatio‐temporal distributions of 91 bee species show that seasonal patterns of abundance and species richness in human‐altered landscapes varied significantly less compared to natural habitats in which floral resources are relatively scarce in the dry summer months. These findings demonstrate that anthropogenic environmental changes in urban and agricultural systems, here mediated through changes in plant resources and water inputs, can alter the temporal dynamics of pollinators that depend on them. Changes in phenology of interactions can be an important, though frequently overlooked, mechanism of global change.